2007
DOI: 10.1021/ol701687m
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Okadaic Acid as a Pathway to the Cell

Abstract: The polyether toxin okadaic acid (OA) inhibits several protein serine/threonine phosphatases that play central roles in the regulation of many essential cellular processes. The use of scanning tunneling microscopy (STM) shows that dimerization of such toxins is crucial to understand the mechanism of toxin transport across model membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Daranas et al . [268] found that the OA molecules can pass lipid bilayers, and consequently cell membranes, after the acid ions are partially neutralized by forming dimers with potassium atoms. Blue mussels ( M. edulis ) can take up azaspiracids (AZAs), which are slightly more apolar than OA, mainly via the gill, but the toxins may have been adsorbed on the surface of microflagellates given as food [269].…”
Section: Uptake Accumulation Detoxification and Enzymatic Transmentioning
confidence: 99%
“…Daranas et al . [268] found that the OA molecules can pass lipid bilayers, and consequently cell membranes, after the acid ions are partially neutralized by forming dimers with potassium atoms. Blue mussels ( M. edulis ) can take up azaspiracids (AZAs), which are slightly more apolar than OA, mainly via the gill, but the toxins may have been adsorbed on the surface of microflagellates given as food [269].…”
Section: Uptake Accumulation Detoxification and Enzymatic Transmentioning
confidence: 99%
“…However, such measurements do not discard the existence of minor populations of monomers and/or tetramers. Considering that we have successfully used scanning tunneling microscopy (STM) to confirm the existence of dimeric forms of OA [22], we decided to follow a similar approach to confirm the existence of its tetrameric forms. In order to do this, a gold plate was dipped into a methanol solution of OA (10 mg/mL) and as expected, a gold surface mainly covered by 40–45 Å particles that correspond to OA dimers (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Using this technique it is possible to measure particle sizes, therefore it was feasible to differentiate between particles formed by one or two units of OA, therefore the formation the dimers mediated by K + ions was verified (Figure 3). Subsequently, a simplified model to study the transport of the toxin through a lipid bilayer was built separating two KCl aqueous solutions by a lipid bilayer [22]. One solution had the K + concentration that can be found in the intracellular medium (100 mM) while the other contained 0.5 mM of OA and 5 mM of the same electrolyte (equivalent to the extracellular concentration).…”
Section: Dimerization Of Okadaic Acid Overviewmentioning
confidence: 99%
“…The hydrophobic groove is exposed at the surface. MCLR and TM have similar structures, with three features in common: a carboxyl group, a hydrophobic tail, and a large macrocyclic domain (26). MCLR binds to PP1 in such a way as to interact with three distinct regions of the surface: the metal‐binding site, the hydrophobic groove, and the edge of the C‐terminal groove near the active site.…”
Section: Discussionmentioning
confidence: 99%